KEDUDUKAN HUKUM PERJANJIAN PENGIKATAN JUAL BELI APABILA SALAH SATU PIHAK MENINGGAL DUNIA - Novieyani Wiratmaja (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2023)
The binding sale and purchase agreement (PPJB) for land rights is a preliminary agreement on the topic of sale and purchase of listed land rights, but the format is limited to a legally binding agreement signed by a notary. Prior to the Sale and Purchase Deed (AJB) made by the Land Deed Making Officer (PPAT), PPJB was often implemented to provide legal certainty to the parties involved in the land transfer process. This study aims to analyze the legal position of the PPJB if one of the parties dies and the legal protection in the binding sale and purchase agreement for one of the parties who dies. This research is normative legal research using a conceptual approach and a statutory approach. The results of this study indicate that:First,PPJB's position as a preliminary agreement in buying and selling land contains promises from the parties which contain clauses that determine when the conditions for the sale and purchase have been fulfilled.Second,the legal protection provided by PPJB is paid off and the power to sell if the seller dies is perfect and as strong evidence, because it is made in the presence of an authorized public official, namely a Notary. Meanwhile, legal protection for PPJB has not been paid off by considering the redaction of the conditions listed in the PPJB as a preventive measure in protecting buyers and sellers.Keywords: Position, Binding, Buying and Selling